The problem of academic gender mobbing in turkish universities (Revista de Investigaciones Universidad del Quindío, 2022)
The issue of academic mobbing is growing at an alarming rate in Turkish universities. This is a negative practice whereby outspoken and ethical scholars are attacked. These scholars are always kicking against bad practices in society. They possess knowledge that most people consider intimidating. These actions are usually initiated by their lesser administrators and colleagues. Based on this, it is crucial to know how this problem starts and deteriorates among colleagues. This research study will be aiming to determine mobbing behavior prevalence as exposed by superiors, the dean and heads of departments. Various subtopics will be analyzed and discussed in this paper like faculty outcomes, ethics, and envy twinge. These are all related to rectors, university presidents, provosts, department chairs, deans, policymakers, academic leaders, researchers, academicians, and many others.
Keywords: Gender; Mobbing; Turkish Academic Environment; Workplace Problems